The effect of chronic disease on food stress among the low-income polulations in Cyprus - Chrysostomou, Stavri; Andreou, Sofia N.; Giannakou, Konstantinos (My University, 2022)
Background Food stress can be defined as the product of the cost of healthy food relative to the income of the household and occurs when households spend 30% or more of their income on food costs. Objectives To examine the effect of chronic disease on food stress among low-income population in Cyprus. Methods Three Food Baskets were developed for two different types of households (men and women). Healthy Food Baskets (HFB) were constructed based on the National Guidelines for Nutrition and Exercise. The Gluten Free Healthy Food Baskets (GFHFB) were based on the HFB and all products containing gluten were replaced with gluten free products. The Diabetic Healthy Food Baskets (DHFB) were based on the HFB and the guidelines of the American Diabetes Association (ADA). Affordability was defined as the cost of each basket as a percentage of the Guaranteed Minimum Income (GMI). The value of the GMI is set to be equal to C¼ 480 for a single individual and increases with the size of the recipient unit accordance to the Organization for Economic Co-operation and Development equivalence scales. Results The monthly cost of the HFB for a man is 258.8 euros and for a woman is 187.1 euros. Also, a healthy man on GMI would need to spend 53.9% of his income on the HFB whereas the relative percentage for a healthy woman is to equal to 39%. The monthly cost of the GFHFB is about 16% (47 euros) and about 17% (33.6 euros) more expensive compared to the HFB for man and woman, respectively. Adults with celiac disease receiving GMI would need to spend 59.5% and 41.9% of their income on the GFHFB (man and woman, respectively). Moreover, the total monthly budget for a diabetic man is 16% (37.6 euros less) lower compared to the HFB and the relative percentage for the diabetic woman is about 15% (25.7 euros less). Moreover, for low-income adults with diabetes the proportion of income that would need to be spent on the DHFB is 50.1% and 35% for man and woman, respectively. Conclusion The HFB, the GFHFB and the DHFB are characterized by low affordability causing food stress among the low-income population in Cyprus. Notably, healthy and nonhealthy men seem to experience higher level of food stress compared to women. Moreover, results of the current study indicate that the occurrence of a chronic disease has a different impact on food stress